Propuesta de implementación de un planeamiento tributario y su incidencia en la situación económica y financiera de la empresa agroindustrial Casagrande S.A.A - Ballena Campos, Mercedes Tatiana (2017)
Over the years the Tax Administration has become the shadow of small and large taxpayers, that shadow that is always pending of the movements that can carry out the company, for this reason the present research project considers to make a proposal of Implementation of a Tax Planning to evaluate its impact on both the economic and financial situation of the Agroindustrial Casagrande SAA Considering both the theoretical tools and the information of the Financial Statements and of the programs and calculations of taxes that the company realizes, recognizing that it is in the Agrarian Regime and whose provision contemplates the benefits for the development of its operations . The present study analyzed the economic and financial situation of the company based on the year 2015, clearly observing the taxes to which it is subject and its incidence in the Financial Statements of the aforementioned company, also shows a projection for the period 2016, With the application of the proposed planning, with the new policies that must adapt the company to make the calculation and payment, timely and efficient of the taxes under the legally accepted regulations avoiding future contingencies, as well as the unnecessary payment of fines that we can be Subjects as a consequence of some control.